Bioensaios ecotoxicológicos em águas superficiais da região metropolitana de Maceió usando Zebrafish (daniorerio) como modelo animal - Santos, Orlando Ronaldy da Silva (2019)
Water quality is currently a major concern on a global scale and considered as a vital parameter for the maintenance of ecosystems, in addition to its great impact in terms of Public Health.Toxicological evaluation of water is important in water quality studies. Bioassays are an efficient way of assessing the impact of substances on biological systems and, in this context, zebrafish is a well-stablished animal model for toxicological assessments. Surface waters of the State of Alagoas lack toxicity evaluation studies. Thus, the present study aims to evaluate the water quality of surface bodies (Pratagy River and Catolé Dam) used as source for catchment, processing and distribution in the Water System of the Alagoas Metropolitan Region, through physical-chemical and microbiological tests for identification and quantification of contaminants, as well as in vivo exposure assays for neutoxicity assessment through a videomonitoring based technique. Analysis of pH, turbidity, apparent color, salinity, dissolved solids, hardness, conductivity, ammonia, nitrite, nitrate, metals, residual chlorine, sulfate, dissolved oxygen, biochemical oxygen demand (BOD), chemical oxygen demand (COD) indicated that the raw water samples obtained from the two selected sources of water demonstrate parameters in disagreement with Brazilian legislation. No traces of pesticides were detected in gás chromatography mass spectrometry (GC-MS) analysis, however,inductively coupled plasma mass spectrometry (ICP-MS) analysis revealed the presence of potentially toxic metals in both types of water, raw and treated.Our zebrafish bioassays revealed that waters containing the identified substances are capable of inducing neurological alterations in vivo, directly affecting the behavior of exposed fish (p<0.05),which indicates the need of conducting periodic toxicological studies to ensure its safety to the population served and the control of possible environmental damage.